Bacterial Flora and Antibiotics Sensitivity Pattern in Chronic Rhinosinusitis Outpatient Cases in Tertiary Care Hospital - Shrestha, D. (Kathmandu University Medical Journal, 2022)
Background Chronic rhinosinusitis is a disease that afflicts a significant percentage of the population and causes considerable long-term morbidity. The initial treatment is clinical evaluation followed by starting empirical antibiotics. With the use of empirical antibiotics there is a possibility of aggravating the disease and leading to the persistence of chronic sinusitis. In order to start a protocol for rational use of antibiotics, we need to have the bacteriological profile in cases of chronic rhinosinusitis along with the sensitive group of antibiotics. Objective To determine the bacterial flora in nasal swab of patients with chronic rhinosinusitis and identify the sensitive antibiotics for the bacterial isolate. Method A prospective, cross-sectional study was conducted in ENT Head and Neck Department of tertiary care hospital. The study population was the patients with clinical diagnosis of chronic rhinosinusitis whose nasal swabs were taken during nasal endoscopy and sent for culture and sensitivity. The data were entered in Microsoft Excel and analyzed using statistical computer program Statistical Package for the Social Sciences (SPSS). The ethical approval for the study was taken from Ethical Committee of Kathmandu Medical College. Result There were 60 (87%) bacterial isolate growths out of 69 samples of which 49 (82%) were gram positive and 11 (18%) were gram negative. The most common bacteria isolated was S aureus (42%) followed by Cogaulase neagative Staphylococcus (25%). Conclusion Among gram positive isolates, amoxycillin was the most sensitive antibiotic and among gram negative isolates, ceftriaxone, levofloxacin, imipenem, meropenem and piperacillin were most sensitive antibiotics. In this study, we have determined the bacterial flora from endoscopic nasal swab of the sinuses in chronic rhinosinusitis patients and identified the sensitive antibiotics. This study would help us prescribe rational antibiotics in cases of chronic rhinosinusitis.